Gaya Komunikasi Guru dan Dampaknya Terhadap Kesehatan Mental Siswa - Aghis Nayla Zahara; Abdurohim (PT. Hasba Edukasi Mandiri, 2025)
This study aims to identify the communi cation styles used by teachers and analyze their impact on students’ mental health. In the context of modern education, effective communication between teachers and students is a crucial factor, not only in supporting the teaching and learning process but also in promoting students’ psychological well-being. This research employs a qualitative descriptive approach, using interviews, questionnaires, and observations as data collection techniques. The results indicate that the democratic communication style is the most commonly applied by teachers and has a positive impact on students’ mental health, such as reducing stress and increasing self-confidence. Conversely, the authoritarian style tends to have negative effects, leading to pressure and anxiety. These findings highlight the importance of teacher training in developing supportive communication styles to foster a mentally healthy learning environment.